El control interno del Área de Almacén y la rentabilidad de la Empresa Industrial Yefany Inversiones S.A.C. periodo 2013. - Mendoza Flores, Misael (2014)
This thesis focuses on the search for information to determine what was the behavior of internal management in warehouses of Industrial Company “YEFANY INVERSIONES S.A.C. " and its influence on the profitability of it. In order to establish the causes that would result in increased profitability, internal control is evaluated in the warehouse area , to determine factors that are generating increases in production costs reflected in the financial information for the periods 2010 - 2013 , which does not allow to increase the profitability of the company. The investigation is a descriptive model, as it will delve into the data collection and then provide results to the Management Company for making decisions regarding internal policies for better management. The methodology used was the comprehensive analysis of quantitative and qualitative data collected in addition to the Financial Reporting Finals engaged in this investigation periods , for which a tally sheet was designed to collect information, reports were also reviewed Work annual staff mentioned area . Among the most important results cast after having made all appropriate analysis through data collection instruments and financial assessment of profitability through financial ratios , induces an efficient internal control storage area influences the increase profitability , since when properly implement the policies and internal control guidelines for storage area is managed to reduce production costs generated by ordering , returns low quality merchandise , plus the little guidance of human talent ; this causes delays in production and therefore delays in delivery of orders, hurting the profits earned by the company. The financial evaluation of the company YEFANY INVERSIONES S.A.C, through rates of return applied to the periods 2010 - 2013 to conclude that the company has reduced its earnings from one period to another, noting reductions in profitability due to increased production costs mainly. some aspects are recommended , among the most important are : implement policies internal investigation, which explains the importance of quality , relevance and benefit to have efficient warehouse management for the company YEFANY INVESTMENT SAC , and it should be clarified also , it is important to control future regulations issued for better management of the warehouse of raw materials and the finished production , achieving efficiency levels define the value chain of the business, maximizing profit margins and above earnings for the Company and the industry in general.